Current State of the Development of Therapies for Emergency Prophylaxis and Treatment of Ebola Virus Disease - A. A. Petrov; V. N. Lebedev; T. M. Plekhanova; L. F. Stovba; G. V. Borisevich; O. N. Sidorova; O. V. Chukhralya; S. V. Borisevich (Проблемы особо опасных инфекций, 2015)
Nowadays vaccination of the population living in the endemic regions and widespread implementation of the potent therapies for the emergency prophylaxis and treatment into the clinical practice are regarded as the basic efficient and cost-effective measures for Ebola epidemic spread control. Objective of the review is to analyze current state of the development of aids for the immediate prophylaxis and treatment of Ebola fever. Focus area of the activities is the construction of drugs on the basis of virus-specific anti-bodies (including monoclonal), small interfering RNA, and anti-sense phosphordiamidate morpholine oligomers and interferons. The paper discusses the most significant achievements in this sphere.